HBV inhibits apoB production via the suppression of MTP expression - Wang Fu-Bing (Lipids in Health and Disease, 2011)
Abstract Background Liver dominates the production and secretion of apolipoprotein B (apoB) and evidence shows that liver malfunction induced by hepatitis B virus (HBV) infection could lead to apolipoprotein metabolism disorders. The present study was undertaken to assess the effects of HBV on apoB expression. Methods Clinical examination: serum apoB levels in patients with chronic HBV infection and in healthy individuals were measured by immunoturbidimetry using biochemical analyzer Olympus 5400. Cell study: mRNA and protein expression levels of apoB in HepG2 and HepG2.2.15 cells were measured by RT-PCR and Western blot. Alternatively, HBV infectious clone pHBV1.3 or control plasmid pBlue-ks were tranfected into HepG2 cells, and mRNA and protein expression levels of apoB, as well as the microsomal triglyceride transfer protein (MTP) in tranfected HepG2 cells were also measured by RT-PCR and western blot. Results Serum apoB level was much lower in chronic HBV patients as compared to healthy individuals (P < 0.05). Expression of apoB mRNA and protein was lower in HepG2.2.15 cells than in HepG2 cells. Similarly, expression of apoB mRNA and protein was lower in pHBV1.3 transfected HepG2 cells than in pBlue-ks transfected HepG2 cells. Expression of MTP mRNA and protein in pHBV1.3 transfected HepG2 cells was reduced in a dose-dependent fashion. Conclusion HBV infection plays an inhibitory effect on apoB expression.